Research and development, welfare and efficiency: an Australian energy perspective. (1998) - Islam, Sardar M.N.; Sheehan, Peter
This paper uses a dynamic multi-level optimisation model to provide evidence for the proposition that policy interventions, which may include support for R&D, are required in the Australian energy sector to maximize economic welfare. The optimum research and development strategies emerging from the model results, emphasise work on energy conservation and efficient energy conversion techniques. These strategies are consistent with the underlying energy policy stance adopted in the Australian economy over the past decade.